Supplier Performance Evaluation and Selection on Apple Agro-Industry - Silvana Maulidah; Djoko Koestiono; Taufik Rizal Dwi Adi Nugroho (Agriekonomika, 2021)
Understanding supplier performance is very vital to ensuring a well-functioning of apple agro-industry supply chain network. It will help the process of potential supplier sevaluation and selection, it is also improving both the performance of firms and its suppliers. The purposes of this research are to evaluate the performance and select the potential of apple supplier. The results of this study are as follows: categories (drivers) priority for the evaluation of apple supplier performance are price (0.406), quality (0.335), delivery (0.130) and services (0.070). Based on that categories, the selection of potential of apple supplier sequentially areSupplier A (0.429), Supplier C (0,316), Supplier D (0.129) and Supplier B (0.125). Hopefully, the apple agro-industry can determine the best of suppliers in fulfilling their raw material.